Strategi Perencanaan Model Bisnis Perusahaan Jasa Konsultan Arsitektur dan Jasa Kontraktor PT Architectaria Media Cipta - Amin, Amirullah Muh; Baga, Lukman M; Tinaprilla, Netti (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
PT Architectaria Media Cipta is an architectural consulting and contractor company.The purpose of this research is to describe and improve the business model used by PT Architectaria Media Cipta based on Business Model Canvas (BMC) approach and SWOT analysis, and then develop a new business model prototype for PT Architectaria Media Cipta using Blue Ocean Strategy (BOS).BMC consist of customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. The data collected bystructured interview.There are seven unsurts that need to be improved in a major way, and the two unsurts are remedied in a minor.The new business model prototype is created with a new value proposition that makes home and office furnishings products with unique designs, fixed size, light weight that can be sold massively through webstores and marketplace. Innovative products made by utilizing waste materials with the concept of re-use and re-cycle, therefore) the selling price of the product remains affordable.